Biological agents in psoriatic arthritis - Kocijan, Roland; Muschitz, Christian; Rech, Juergen (Wiener Medizinische Wochenschrift, 2015)
Anti-tumor necrosis factors (TNFs) are effective drugs for the treatment of psoriatic arthritis (PsA) regarding reduction of pain and inflammation, enthesitis, dactylitis, as well as psoriatic skin and nail disease. Moreover, radiographic progression in PsA is decelerated. The efficacy of anti-TNFs seems to be independent of synthetic disease-modifying anti-rheumatic drugs, suggesting only a minor role of combination therapy in PsA. Anti-TNFs are generally well tolerated in patients with PsA. Adverse events are similar to those reported in patients with rheumatoid arthritis. Ustekinumab, a recently approved IL-12/IL-23-antibody is another promising biological agent in the treatment of PsA.
EVALuna2:13077